The Thursday murder club (Thursday Murder Club novels, 1, 1, 2020)
"In a peaceful retirement village, four unlikely friends meet weekly in the Jigsaw Room to discuss unsolved crimes; together they call themselves The Thursday Murder Club. There's Red Ron, the infamous former socialist firebrand, still causing trouble; gentle Joyce, widowed, pining for another resident, but surely not as innocent as she seems; Ibrahim, a former therapist who understands the darker side of human nature; and Elizabeth? Well, no one is quite sure who she really is, but she's definitely not a woman to underestimate. When a local developer is found dead, the Thursday Murder Club suddenly find themselves in the middle of their first live case. The friends might be septuagenarians, but they are cleverer than most. Can our unorthodox but brilliant gang catch the killer before its too late?

The man who died twice: a Thursday Murder Club mystery (Thursday Murder Club novels, 2, 1, 2021)
When an old friend, who has been accused of stealing millions of dollars' worth of diamonds, desperately needs her help, Elizabeth and her friends go up against a ruthless murderer who wouldn't bat an eyelid at knocking off four septuagenarians.

The bullet that missed: a thursday murder club mystery (Thursday Murder Club novels, 3, 1, 2023)
INSTANT NEW YORK TIMES BESTSELLERA new mystery is afoot in thethird bookin the Thursday Murder Club series from million-copy bestselling author Richard Osman."The quartet of aging amateur sleuths.remain wonderful company," -the New York Times Book Review "The Bullet That Missed hits on every front." -the Wall Street JournalIt is an ordinary Thursday, and things should finally be returning to normal. Except trouble is never far away where the Thursday Murder Club are concerned. A decade-old cold case-their favorite kind--leads them to a local news legend and a murder with no body and no answers.Then a new foe pays Elizabeth a visit. Her mission? Kill or be killed. Suddenly the cold case has become red hot.While Elizabeth wrestles with her conscience (and a gun), Joyce, Ron, and Ibrahim chase down the clues with help from old friends and new. But can the gang solve the mystery and save Elizabeth before the murderer strikes again?From an upmarket spa to a prison cell complete with espresso machine to a luxury penthouse high in the sky, this third adventure of the Thursday Murder Club is full of the cleverness, intrigue, and irresistible charm that readers have come to expect from Richard Osman's bestselling series.

The last devil to die: a Thursday murder club mystery (Thursday Murder Club novels, 4, 1, 2023)
It's rarely a quiet day for the Thursday Murder Club. Shocking news reaches them--an old friend has been killed, and a dangerous package he was protecting has gone missing. The gang's search leads them into the antiques business, where the tricks of the trade are as old as the objects themselves. As they encounter drug dealers, art forgers, and online fraudsters--as well as heartache close to home--Elizabeth, Joyce, Ron, and Ibrahim have no idea whom to trust. With the body count rising, the clock ticking down, and trouble firmly on their tail, has their luck finally run out? And who will be the last devil to die?